1920. Ocular Involvement in Candidemia Patients at an Urban Tertiary Care Center: Is Inpatient Ophthalmologic Consultation Essential?. (26th November 2018) - Brunner, Robert; Min, Zaw; Abdulmassih, Rasha; Bhanot, Nitin
Abstract: Background: Visual loss is a feared consequence of candidemia. The IDSA recommends dilated eye examination for all patients diagnosed with candidemia, irrespective of symptoms. Approximately 1% of patients with candidemia have ocular involvement. Given the low incidence, we posit that inpatient ophthalmologic consultation may not be required for every candidemic patient. Methods: We retrospectively reviewed records of all patients with candidemia from June 2015 to March 2017. Age, gender, comorbidities, time to initiation of antifungal treatment, Candida species and choice of antifungal medication were recorded. We also obtained time to ophthalmology consultation and associated cost. Results: A total of 120 patients with candidemia were identified (mean age 61; 62% male, 38% female). Seventy-nine percent had an indwelling venous catheter, 37% had DM, 24% were immunosuppressed, 16% had CKD, 14% were receiving TPN, and 15% were IVDU. Ninety-five percent of patients had received antibiotics in the previous 30 days. Twenty-six percent had undergone major surgery in the preceding 90 days. The majority of isolates were Candida albicans (46%). Average duration of candidemia was 4 days (range 1–18). Of the 120 patients, 73 (60%) underwent Ophthalmology evaluation. Two of those patients (2.7%) endorsed ocular symptoms, but only one had objective ocular involvement (retinitis without vitritis) which did not necessitate intravitreal therapy or surgery. The majority of our patients (68%) were treated with fluconazole. Initiation of antifungal therapy ranged from the day candidemia was diagnosed to 5 days later. Time to Ophthalmology consultation (from the time consult was requested) ranged from 1 to 9 days. Total cost for all ophthalmology consultations approximated $22, 000. Conclusion: Ocular involvement was rare in our study. No change in short-term management was made based on ocular findings. However, there was substantial cost associated with inpatient ophthalmology consultation and probably with length of stay in patients awaiting eye examination. Hence, we suggest that inpatient eye evaluation may be reserved for patients with ocular symptoms (and those unable to verbalize complaints) as long as outpatient ophthalmology examination can be arranged. Disclosures: All authors: No reported disclosures.